2019
DOI: 10.1097/md.0000000000016716
|View full text |Cite
|
Sign up to set email alerts
|

Association of GTF2I gene polymorphisms with renal involvement of systemic lupus erythematosus in a Chinese population

Abstract: The purposes of the study was to validate the relationship between General transcription factor II-I (GTF2I) genetic variants and kidney involvements of systemic lupus erythematosus (SLE) patients in a Chinese Han population. Samples from 400 SLE patients and 400 age- and sex-matched healthy controls were collected and genotyped by improved multiplex ligation detection reaction technique. The relationship between gene polymorphism of rs117026326, rs73366469, and susceptibility, progression of SLE we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Our previous GWAS showed that GTF2I was the most strongly associated gene in Chinese Han patients with primary Sjögren’s syndrome (pSS) ( 23 ). Several association studies of candidate genes have revealed that the GTF2I gene is an important genetic susceptibility factor in SLE and RA ( 7 , 24 ). Furthermore, SSc, pSS, SLE, and RA are all connective tissue diseases and share many clinical features, particularly in aspects of immune activation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous GWAS showed that GTF2I was the most strongly associated gene in Chinese Han patients with primary Sjögren’s syndrome (pSS) ( 23 ). Several association studies of candidate genes have revealed that the GTF2I gene is an important genetic susceptibility factor in SLE and RA ( 7 , 24 ). Furthermore, SSc, pSS, SLE, and RA are all connective tissue diseases and share many clinical features, particularly in aspects of immune activation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indeed confirmed that GTF2I SNPs rs117026326 and rs73366469 were strongly associated with SSc in the Chinese Han population. Interestingly, rs73366469 is located within conserved enhancers and overlaps with transcription start sites (TSS) for GTF2I , thereby demonstrating the meaningful regulation of GTF2I ( 24 ). Additionally, rs117026326 and rs73366469 displayed consistent allele, genotype, genetic model, and clinical association results because of their medium linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…1 b, Table 2 ) in Thai population, and the variants at the PROS1C1 , NOTCH4 , HCP5 , C6orf10 , TAP2 , TNFSF4 , RasGRP3 , TERT , TNPO3-IRF5 , CXCR5 , GPR19 , SLC15A4 , and ITGAM loci showed suggestive evidence of associations with SLE ( p value < 5E−05, Supplementary Table 1 ). These loci have been found in several ancestries, including Han Chinese, Korean, North American, European, African, and Hispanic populations [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these loci, the HLA-DQA1, HLA-DRB1, STAT4, FAM167A-BLK, and GTF2I loci have reached the genome-wide signi cant threshold (p-value < 5E-08; Figure 1B, Table 2) in Thai population, and the variants at the PROS1C1, NOTCH4, HCP5, C6orf10, TAP2, TNFSF4, RasGRP3, TERT, TNPO3-IRF5, CXCR5, GPR19, SLC15A4, and ITGAM loci showed suggestive evidence of associations with SLE (p-value < 5E-05, Supplementary Table 1). These loci have been found in several ancestries, including Han Chinese, Korean, North American, European, African, and Hispanic populations [30,31].…”
Section: Resultsmentioning
confidence: 99%